COLLABORATIVE PEDAGOGY IN PHILOLOGY: THE ROLE OF PEER EXCHANGE IN SHAPING EFFECTIVE TEACHING PRACTICES (Web of Teachers: Inderscience Research, 2024)
This article studies the role of peer exchange within professional learning communities (PLCs) as a framework to enhance effective teaching practices. In the context of philology, collaborative teaching methodologies promote the exchange of insights, resources, and innovative techniques among educators, reinforcing both disciplinary expertise and pedagogical skills. Drawing on evidence from PLC studies and collaborative frameworks in higher education, this paper argues that such communities foster reflective dialogue and joint problem-solving, which are essential for addressing the complexities of language teaching and learning. Key characteristics of effective PLCs—such as reflective practice, shared goals, and mutual accountability—emerge as central to improving teaching strategies and student outcomes. The analysis highlights how collaborative learning, both in physical and digital spaces, contributes to teachers’ professional growth and collective responsibility, ultimately leading to enhanced teaching practices in philology. This approach underscores the significance of shared professional learning in adapting and refining philological instruction to meet contemporary educational demands.